Teachers’ Pedagogical Competence and Its Impact on Students’ Religious Attitudes in Islamic Religious Education Learning - mastur (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2026)
Abstract This study examines the impact of teachers’ pedagogical competence on students’ religious attitudes in Islamic Religious Education learning. Adopting a mixed-methods approach, data were collected through questionnaires, classroom observations, and interviews. The results indicate that teachers’ mastery of instructional strategies, classroom management, and student-centered learning significantly influences students’ religious understanding and attitudes. Effective pedagogical competence encourages reflective religious practices rather than rote learning. The study highlights the central role of teacher professionalism in shaping meaningful religious education. These findings provide empirical evidence for improving teacher training programs and enhancing the quality of Islamic Religious Education.